Digital Distractions with Peer Influence: The Impact of Mobile App Usage on Academic and Labor Market Outcomes - Panle Jia Barwick; Siyu Chen; Chao Fu; Teng Li (The Quarterly Journal of Economics, 2026)
Abstract Concerns about excessive mobile phone use among youth are mounting. We present estimates of behavioral and contextual peer effects, along with comprehensive evidence on how students’ own and their peers’ app usage affect academic performance, physical health, and labor market outcomes. Our analysis draws on administrative data from a Chinese university covering three student cohorts over four years. We exploit random roommate assignments, differential exposure to a policy shock (gaming restrictions for minors), and differential exposure to a discrete event (the introduction of a blockbuster video game) for identification. App usage is contagious: a one s.d. increase in roommates’ in-college app usage raises own usage by 5.8%. High app usage is harmful across all measured outcomes. A one s.d. increase in app usage reduces GPAs by 36.2% of a within-cohort-major s.d. and lowers wages by 2.3%. Roommates’ app usage reduces a student’s GPA and wages through both disruptions and behavioral spillovers, generating a total negative effect that exceeds half the magnitude of the impact from the student’s own app usage. Extending China’s three-hour-per-week gaming restriction for minors to college students would boost their initial wages by 0.9%. High-frequency GPS and app usage data show that heavy app users spend less time in study halls, are more frequently late or absent from class, and get less sleep.